Given that x = − 9 is a root of ∣ ∣ ∣ ∣ ∣ ∣ x 2 7 3 x 6 7 2 x ∣ ∣ ∣ ∣ ∣ ∣ = 0 the other two roots are x = α and x = β . Find 5 + ⌊ 3 α + β ⌋ .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The above determinant computes to:
x 3 − 6 7 x + 1 2 6 = ( x + 9 ) ( x − α ) ( x − β ) = x 3 − ( α + β − 9 ) x 2 + ( α β − 9 α − 9 β ) x + 9 α β = 0
By Vieta's Formulae, we obtain:
α + β − 9 = 0 ; α β − 9 α − 9 β = − 6 7 ; 9 α β = 1 2 6 ⇒ β = α 1 4
and now taking α + α 1 4 − 9 = 0 ⇒ α 2 − 9 α + 1 4 = ( α − 2 ) ( α − 7 ) = 0 ⇒ α = 2 , 7 .
This gives the points ( α , β ) = ( 2 , 7 ) ; ( 7 , 2 ) as solutions, which makes 5 + ⌊ 3 α + β ⌋ = 8 .
I mean like is there a shorter way of reducing this determinant like subtracting the rows/columns method.Because otherwise we have to directly use the co-factor sum ,and expanding along row R 1 we get cubic x 3 − 6 7 x + 1 2 6 = 0 .And it can be factored to ( x + 9 ) ( x 2 − 9 x + 1 4 ) = 0 clearly the sum of the other 2 roots is − b / a = 9 .Hence answer is 5 + 3 = 8 .
Problem Loading...
Note Loading...
Set Loading...
consider the matrix
A = ⎣ ⎡ 0 2 7 3 0 6 7 2 0 ⎦ ⎤
the charactestic equation of the matrix is given by
det ( A − λ I ) → ∣ ∣ ∣ ∣ ∣ ∣ − λ 2 7 3 − λ 6 7 2 − λ ∣ ∣ ∣ ∣ ∣ ∣ = 0 = 0
we can get the required equation by using the transformation λ = − x
also we have sum of roots of characterstic equation = t r a c e ( A ) = 0
the sum of roots of given equation will be ∑ i = 0 3 − λ i = − ∑ i = 0 3 λ i = 0
Thus α + β = 9
5 + ⌊ 3 α + β ⌋ = 5 + 3 = 8